ELAZIĞ İLİNDE ARICILIĞIN YOĞUN OLDUĞU YÖRELERİN BALLARINDA POLEN ANALİZLERİ - GÜR, NAZMİ (Fırat Üniveristesi, 1993)
Bu çalışrrmda, Elazığ İlinde arıcılığın yoğun olarak yapıldığı 7 bölgeden toplanan ballarda polen anali2i yapılmıştır. Bala nektar veren bitkiler, balda bulunan polenlerin teşhisi yapılarak belirlenmiştir. Her bir örnekten alınan 10 gr. balda bulunan polenlerin toplam miktarı ve her taksamın ayrı ayn polen miktarı hesaplanmıştır. Bal örneklerindeki polenlerin tanımlanması sonucu 9 familyaya ait 1 8 değişik bitki tespit edilmiştir. Ayrıca balların fiziksel özelliklerinden kristalleşmenin olup olmadığı ve renginin açık veya koyu oluşu da belirlenmiştir. Elazığ ili ballarında yapılan polen analizleri sonucunda, Achillea, centaurea triumfetti, Xeranthemum, Carduus, Helianthus annuus, Astragalus, Trifolium, vicia, onobrychis, Daucus, Vitis, Feganum harmala. Salvia, Mentha, Prunus, Rubus, Eleagnus angustifolia bala nektar veren bitkiler olarak tespit edilmiştir. ANAHTAR KELİMELER : 'Bal, Polen, Melitopalinoloji

SUMMARY Maştlier Thesis POLLEN ANALYSIS IN HONEY SAMPLES FROM AREAS OF INTENSIVE APICULTURE IN ELAZI? REGION Nazmi 6ÜR Fırat University, Graduate School of Natural and Applied Sciences Department of Biology 1993, Page: 29 In this research work, the polen analyses have been conducted in honey sarnies wich were collected from 7 localities where apiculture has Intensively been practised. The pollen analyses led to the determi nation of trie plants from which nectar of the honey samples have been derived. The total number of the pollen numbers of each taxa have been calculated. Upon pollen analyses, 1 8 different plants belonging to 9 families have been determined. The physical features of the honey samples, including the crystallization and colour, have been recorded. Upon pollen analyses, the plants contributing nectar to honey samples m Elazığ have been found as follows Achilles, Ccritsvrcs, trivmfetii, Xcrsrithsmuna, Csrduus, Hslisrthvs snttttus, Astrsgslus, Tri folium, ¥icis, Ombrychis, Dsucus, Yitis, Pegsnum hsrmsls, Sshis, tenths, Prtmvs, Rubus, Elesgntts srtgustifolis. Key Words : Honey, Pollen, Melitopalynology
Keywords: Botanik; Botany